The concept of chosenness in Judaism and Christianity : a comparative analysis - Ros Izanie binti Ismail (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
The concept or doctrine of chosenness is mutually exclaimed by Judaism and Christianity. Both religions have their own perspective of chosenness. Chosenness is a significant concept that has shaped the identity of both religions throughout history. Chosenness entails a sense of exclusiveness of the religion and its religious community. The concept could be an important factor in determining the relationship of the Jews with Christians and other religious communities. This research attempts to explore the understanding of chosenness from the point of view of both religions. In consequence the similarities and differences between these two religions in addressing chosenness could be examined. The data and information relevant to Jewish and Christian notions of chosenness are collected and gathered. Apart from books, articles and reliable websites, the important material relied on for the research purposes is the New King James Version Bible. The understanding of both religions on issues related to chosenness namely; covenant, salvation by laws versus salvation by faith, holy land, and exclusiveness versus universal mission are compared and analysed. The research discovers that to a certain extent both religions have similar understanding of chosenness. However they differ on some other points.